2018
DOI: 10.1002/ppsc.201800131
|View full text |Cite
|
Sign up to set email alerts
|

Improving Dielectric Nanoresonator Array Coatings for Solar Cells

Abstract: Antireflection coatings based on dielectric nanosphere arrays are discussed in application to photovoltaic materials including silicon and gallium arsenide. We perform macro- and nanoscale characterization and finite-difference time-domain calculations demonstrating the enhanced optoelectronic properties. A significant absorptivity enhancement is achieved due to the collective resonant coupling of excited whispering gallery-like modes and thin-film interference effects. The resonant coupling is masked in macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…30% enhancement in photocurrent 13 . Whereas, Ha et al demonstrated experimentally more than 30% efficiency gain by using SiO 2 NPs on a GaAs solar cell 14 . These NPs were closely packed and worked as an antireflection coating (ARC).…”
Section: Large Photocurrent Density Enhancement Assisted By Non-absormentioning
confidence: 99%
See 2 more Smart Citations
“…30% enhancement in photocurrent 13 . Whereas, Ha et al demonstrated experimentally more than 30% efficiency gain by using SiO 2 NPs on a GaAs solar cell 14 . These NPs were closely packed and worked as an antireflection coating (ARC).…”
Section: Large Photocurrent Density Enhancement Assisted By Non-absormentioning
confidence: 99%
“…This have captured the attention of scientific community recently and being investigated widely. Dielectric NPs at the front of solar cells have been demonstrated experimentally [10][11][12][13][14][15] and theoretically 8,[16][17][18][19] with improved device performance. Wan et al's TiO 2 NPs coated solar cell exhibited ca.…”
Section: Large Photocurrent Density Enhancement Assisted By Non-absormentioning
confidence: 99%
See 1 more Smart Citation